PELATIHAN DATA ANALYST SEJAK DINI: ANALISIS DATA DENGAN METODE REGRESI LINEAR BERGANDA UNTUK SISWA SMA NEGERI 3 DEPOK - Hidriansjah, Iqri Sulizar Hidriansjah; Ahmad Azzam Al Asyraf; Yogi Laksono; Denny Suryadharma; Sauki; Didin Maulana (JAMAIKA: JURNAL ABDI MASYARAKAT, 2026)
This community service activity was motivated by the low level of data literacy among senior high school students and the limited capacity of teachers to integrate data analysis into classroom learning, despite the growing demand for data processing and analytical skills in the digital era. The purpose of this program was to introduce the concept of a data analyst to students at an early stage through hands-on data analysis practice using the multiple linear regression method, to enhance teachers’ capacity in implementing data-based learning, and to encourage the use of school data to improve educational quality. The implementation method employed a training and mentoring approach in the form of a one-day workshop, which included the preparation of training modules and datasets, delivery of theoretical materials, demonstration of data processing software, group-based practical sessions, and evaluation through observation and questionnaires. The results indicated an improvement in students’ understanding of data analysis concepts and their technical skills in processing data, as reflected by the majority of participants being categorized as highly competent and proficient. The level of satisfaction among participants and the school was also high. In conclusion, data analysis training using the multiple linear regression method was effective in enhancing data literacy and analytical skills of senior high school students and is relevant for sustainable implementation in the school environment. Keywords: Data literacy, multiple linear regression, data analysis training, senior high school students, data-based learning